2005
DOI: 10.1136/sti.2004.010439
|View full text |Cite
|
Sign up to set email alerts
|

Signs and symptoms of urethritis and cervicitis among women with or without Mycoplasma genitalium or Chlamydia trachomatis infection

Abstract: Objectives: To study the prevalence, symptoms, and signs of Mycoplasma genitalium and Chlamydia trachomatis infections in women attending a Swedish STD clinic, accessible for both sexes, and in a group of young women called in the cervical cancer screening programme. Methods: A cross sectional study among female STD clinic attendees in Ö rebro and a study among women called for Papanicolaou smear screening. Attendees were examined for urethritis and cervicitis. First void urine and endocervical samples were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
158
3
15

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(185 citation statements)
references
References 27 publications
9
158
3
15
Order By: Relevance
“…Overall, 16.8% of women and 15.1% of men were found M. genitalium positive. These numbers are higher than results of similar studies of STD clinic attendees (1,3,10,29,38), which could be explained by the facts that our specimen collection was conducted over a rather short time period and the patient population consisted of women (and their partners) who were recruited after being diagnosed with nonviral STDs (36).…”
Section: Discussioncontrasting
confidence: 50%
“…Overall, 16.8% of women and 15.1% of men were found M. genitalium positive. These numbers are higher than results of similar studies of STD clinic attendees (1,3,10,29,38), which could be explained by the facts that our specimen collection was conducted over a rather short time period and the patient population consisted of women (and their partners) who were recruited after being diagnosed with nonviral STDs (36).…”
Section: Discussioncontrasting
confidence: 50%
“…Point prevalence ranged from 0.8-4.1%. Previous cross-sectional studies that included some adolescents found a point prevalence between 3.5-7% [10,17,18]. The difference in point prevalence found here may be attributable to the target population for this project as the young women were not recruited from STD or family planning clinics.…”
Section: Discussionmentioning
confidence: 66%
“…A prevalence study using STI clinic patients failed to find an association with clinical symptoms, but did find that microscopic evidence of infection was associated with M. genitalium detection [20]. A study using female subjects with active STI did find an association between M. genitalium detection and symptoms [21]; while, no association between microscopic signs and M. genitalium was found in a cross-sectional study using female STI clinic subjects [17]. Our data is among the first to present M. genitalium signs and symptoms data using a primary care, non-STI clinic, patient population.…”
Section: Discussionmentioning
confidence: 85%
“…In other studies, different populations with an expected low risk of STIs have been defined as control groups. In a Swedish study 10 none of 59 women aged 22-26 years attending a clinic for a pap-smear were infected, in two Japanese studies pregnant women 24 25 had prevalences of 0% (0/ 80) and 1% (1/90), and in a study from the United Kingdom 26 none of 37 women aged 21-45 years undergoing tubal ligation had M genitalium. In asymptomatic women attending STD clinics, the prevalence was 3% 2 and 5%.…”
Section: Discussionmentioning
confidence: 99%